2021
DOI: 10.3389/fgene.2021.656826
|View full text |Cite
|
Sign up to set email alerts
|

Meta-Analyzing Multiple Omics Data With Robust Variable Selection

Abstract: High-throughput omics data are becoming more and more popular in various areas of science. Given that many publicly available datasets address the same questions, researchers have applied meta-analysis to synthesize multiple datasets to achieve more reliable results for model estimation and prediction. Due to the high dimensionality of omics data, it is also desirable to incorporate variable selection into meta-analysis. Existing meta-analyzing variable selection methods are often sensitive to the presence of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Robust penalization methods have drawn increasing attention in recent years ( Freue et al, 2019 ; Hu et al, 2021 ; Chen et al, 2022 ; Sun et al, 2022 ). In high-dimensional longitudinal studies, incorporation of robustness is more challenging.…”
Section: Discussionmentioning
confidence: 99%
“…Robust penalization methods have drawn increasing attention in recent years ( Freue et al, 2019 ; Hu et al, 2021 ; Chen et al, 2022 ; Sun et al, 2022 ). In high-dimensional longitudinal studies, incorporation of robustness is more challenging.…”
Section: Discussionmentioning
confidence: 99%
“…The availability of raw and processed MS data has be-1 come routine for proteomics studies in recent years, and the construction of a consensus for MS data sharing allowed for the evaluation, reuse and comparative analysis of such data [15] and the consequent integration of information through meta-analysis techniques [16]. Meta-analysis is an efficient strategy for the integration and analysis of datasets from multiple studies and may provide more significant and reliable results [17], [18]. For example, the comparison of independently collected MS datasets allowed the integration of pancreatic cancer proteomic data to uncover proteins relevant to diagnosis and prognosis of pancreatic ductal adenocarcinoma [19], where the authors identified 39 secreted proteins with potential for serving as biomarkers.…”
Section: Introductionmentioning
confidence: 99%
“…There are three main types of meta-analysis methods [16]: meta-analysis based on combining results from different studies (e.g., effect sizes, p values or ranks), metaanalysis based on particular cross-platform normalization and a unified model on multiple datasets without data merging that can account for the joint effects of genes on clinical outcomes. Considering the joint modeling of multiple genes, Li et al [17] proposed metalasso, and then meta-nonconvex methods emerged gradually for solving the heterogeneity problem [18,19]. Thus, we combine the MS-ROMP strategy with meta-analysis techniques to improve the strength across multiple datasets.…”
Section: Introductionmentioning
confidence: 99%